ANALYSIS OF DIFFERENCE IN SALES PRICE OF ARABICA COFFEE CERTIFIED BY SUSTAINABLE AGRICULTURE INSTITUTES RAINFOREST ALLIANCE AND FAIRTRADE IN CENTRAL ACEH (Case Study of Rahmat Kinara Multi-Purpose Cooperative) - Ilma Fitri; Yusak Maryunianta; Riantri Barus; Tavi Supriana (Agric, 2023)
Certification is the judgment of a third party as a liaison between the buyer and the seller, where both parties must meet all of their respective certification criteria or standards. The Rahmat Kinara multi-purpose cooperative is one of the cooperatives engaged in the trade of Rainforest Alliance and Fairtrade-certified Arabica coffee. This study aims to determine the difference between the selling price of Rainforest Alliance and Fairtrade-certified coffee at the Rahmat Kinara multi-purpose cooperative, Pegasing, Central Aceh. This research uses time-series data, analyzed using the Mann-Whittney Test (U Test). The results of the Mann-Whittney Test (U Test) showed a significant value of (0.000) < α 0.05, meaning that there is a significant difference between the selling price of Rainforest Alliance and Fairtrade-certified coffee. Sustainable Agriculture Support at the Rahmat Kinara multi-purpose cooperative improved the quality of the coffee crop (ecologically), helped withstand volatile price changes in global markets (economically), assisted in improving farm management, negotiating leverage, and providing access to premium markets (socially fair).Certification, Rainforest Alliance, Arabica Coffee, Fairtrade